1997
DOI: 10.1016/s0022-5223(97)70001-1
|View full text |Cite
|
Sign up to set email alerts
|

Transmyocardial laser treatment denervates canine myocardium

Abstract: Transmyocardial laser treatment destroys cardiac nerve fibers, which may contribute to the reduced angina pectoris seen clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
2
1

Year Published

1998
1998
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(81 citation statements)
references
References 20 publications
(2 reference statements)
2
76
2
1
Order By: Relevance
“…But only 2 published experimental studies suggest that TMR with Ho:YAG laser destroys cardiac nerve fibers. 29,30 Kwong et al 29 evaluated cardiac afferent nerve function by hemodynamic response to bradykinin application to the laser-treated areas of a canine model. Stoll et al 30 showed that TMR performed in nonischemic porcine heart causes significant HED defects consistent with sympathetic denervation.…”
Section: Discussionmentioning
confidence: 99%
“…But only 2 published experimental studies suggest that TMR with Ho:YAG laser destroys cardiac nerve fibers. 29,30 Kwong et al 29 evaluated cardiac afferent nerve function by hemodynamic response to bradykinin application to the laser-treated areas of a canine model. Stoll et al 30 showed that TMR performed in nonischemic porcine heart causes significant HED defects consistent with sympathetic denervation.…”
Section: Discussionmentioning
confidence: 99%
“…Three hypotheses have been put forward to explain the mechanism of action of TMLR: (1) the channels produced by the laser remain patent and blood flows up them from the endocardial surface during systole 7 ; (2) through neovascularization, production of laser channels stimulates angiogenesis and therefore new blood vessel formation 8 -10 ; and (3) through denervation, the laser treatment affects cardiac visceral afferent nerve fibers, causing a decreased perception of chest pain. 11 In the third case, an effect on myocardial blood flow (MBF) would not necessarily be required.…”
mentioning
confidence: 99%
“…Two other mechanisms have emerged as valid alternatives for the explanation of the clinical improvement: nerve destruction 17 and neovascularisation. Destruction of sensitive nerve fibres of the ischaemic region could decrease anginal symptoms; however, this cannot explain the segmental wall motion improvement observed in both clinical and experimental settings.…”
Section: Discussionmentioning
confidence: 99%